Interactions of lymphotoxin alpha (TNF-beta), angiotensin-converting enzyme (ACE), and endothelin-1 (ET-1) gene polymorphisms in adult periodontitis - Hollá, L I; Fassmann, A; Vasků, A; Znojil, V; Vanek, J; Vácha, J (Journal of periodontology, 2001)
BACKGROUND: Adult periodontitis is a complex multifactorial disease whose etiology is not well defined. To investigate whether the genes encoded within the HLA class III region may confer susceptibility to periodontitis, polymorphisms in the ET-1 and TNF-beta genes were analyzed together with the I/D polymorphism of the ACE gene. METHODS: We determined allele and genotype frequencies of the NcoI bi-allelic polymorphism of the TNF-beta gene, the I/D (insertion/deletion) polymorphism of the ACE gene, and the TaqI polymorphism of the ET-1 gene in 63 Caucasian patients with adult periodontitis and 95 orally healthy controls. RESULTS: We found a significant difference in a 3 locus combination of genotypes between patients and controls (P<0.05). In the next analyses, no significant differences were found in allele frequencies of single genes, but we did find a significant difference in the genotype distribution between cases and controls for TNF-beta (P<0.03). Differences were also observed for 2 locus combinations of ACE and TNF-beta genotypes (P<0.03), and the ET-1 and TNF-beta (P<0.05) genes. Evidence of deviation from Hardy-Weinberg equilibrium was observed in the periodontitis group for TNF-beta, with an absence of the B1B1 homozygotes in patients. CONCLUSIONS: This study is of an exploratory nature. Considering the number of significant results, however, at least a part of the observed associations may obviously be real and our findings suggest that interactions of the TNF-beta, ET-1, and ACE genes may be involved in susceptibility to adult periodontitis.
Keywords: Sequence Deletion; Chi-Square Distribution; Gene Frequency; sekvenční delece; Male; Chromosome Mapping; Lymphotoxin-alpha; homozygot; Genetic Predisposition to Disease; Peptidyl-Dipeptidase A; Risk Factors; odds ratio; Genotype; polymorfismus genetický; statistika jako téma; rozdělení chí kvadrát; Adult; transpozibilní elementy DNA; dospělí; Case-Control Studies; mužské pohlaví; Homozygote; angiotensin konvertující enzym; Endothelin-1; endotelin-1; parodontitida; Polymorphism, Genetic; frekvence genu; Periodontitis; DNA Transposable Elements; lidé; ženské pohlaví; studie případů a kontrol; mapování chromozomů; Humans; rizikové faktory; lymfotoxin-alfa; genotyp; Odds Ratio; Alleles; Female; Statistics as Topic; alely; lidé středního věku; genetická predispozice k nemoci; Middle Aged